Gut Microbiota Dysbiosis in Acute Ischemic Stroke Associated With 3-Month Unfavorable Outcome - Sun, Huanhuan; Gu, Mengmeng; Li, Zhongyuan; Chen, Xiangliang; Zhou, Junshan (Frontiers in Neurology, 2022)
Background Alterations in the gut microbiota after ischemic stroke have been demonstrated, whereas the effect on stroke outcome remains to be established. Methods A total of 132 consecutive patients with acute ischemic stroke were prospectively enrolled. Their gut microbiomes within 24 h of admission were profiled using 16S ribosomal RNA (rRNA) gene (V3–V4 region) sequencing. Microbiota comparisons were made between groups with good outcome (n = 105) and poor outcome (n = 27) based on 3-month modified Rankin Scale scores of 0–2 and 3–6. Propensity score-matching (PSM) analysis was conducted to assess the robustness of our findings. The functional potential was predicted using the Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt). Results Patients in the poor outcome group were characterized by a significant reduction in the alpha diversity (Shannon index, p = 0.025; Simpson index, p = 0.010), an increase in the pathogenic bacteria (e.g., Enterococcaceae and Enterococcus), and a decrease in the short-chain fatty acids (SCFAs)-producing bacteria (e.g., Bacteroidaceae, Ruminococcaceae, and Faecalibacterium) to those with good outcome group (all p < 0.05). Similar results of microbial composition were obtained after PSM. The PICRUSt revealed that the pathway for membrane transport was relatively dominant in patients with poor outcome (p < 0.05). Conclusion This study demonstrated that stroke patients with 3-month poor outcome had baseline gut microbiota dysbiosis featured by increased pathogenic bacteria and decreased SCFAs-producing bacteria.